The use of volcanic ash from the eruption of Mount Kelud in East Java for improving yield of sweet potato grown on a sandy soil - H Melsandi; S Prijono (Journal of Degraded and Mining Lands Management, 2015)
The purpose of this study was to explore the effect of volcanic ash from the eruption of Mount Kelud and compost on the soil properties and production of sweet potato on a sandy soil. The treatments of this study were (a) a combination of and volcanic ash with the proportion of 100: 0, 90:10, 80:20, and 70:30 (% weight), (b) the addition of compost (2.5 and 5 t / ha), and (c) two varieties of sweet potato (Manohara and Ayamurazaki). The soil used in this study is the topsoil (0-30 cm) Psament or sandy Entisol obtained from sweet potato cultivation location in Sumber Pasir Village of Pakis District, South Malang. Ten kilograms of planting medium (soil + volcanic ash) for each treatment was placed in a 15 kg plastic pot. Sixteen treatments arranged in a factorial completely randomized design with three replications.  The results showed that application of Mount Kelud volcanic ash and compost was able to improve soil permeability, soil pH, organic C, and K-total, but did not significantly affect total N content, available P and K total land. The highest fresh tuber weights of 373.51 g / plant or 19.92 t / ha and 393.09 g / plant or 20.96 t / ha for Manohara and Ayumurazaki varieties, respectively, were observed in the treatment of 10% volcanic ash + 5 t compost / ha. The carbohydrate content of Manohara variety was higher than that of Ayamurazaki variety at each treatment. The highest carbohydrate content of the Manohara variety  (23.52%)  was obtained through application of  20% volcanic ash + 2.5 t compost/ha, while that of the Ayamurazaki variety (22.42%) was obtained through application of 30% volcanic ash + 2.5 t/ha.